Determinants of Pouch-Related Symptoms, a Common Outcome of Patients With Adenomatous Polyposis Undergoing Ileoanal Pouch Surgery. Issue 10 (6th October 2020) - Gilad, Ophir; Gluck, N.; Brazowski, E.; Kariv, R.; Rosner, G.; Strul, H.
Abstract : INTRODUCTION: Total proctocolectomy with ileal pouch anal anastomosis (IPAA) is performed in patients with adenomatous polyposis syndromes (APSs). Data regarding pouch outcomes in APS are scarce. The purposes of this study were to determine the prevalence of pouch-related symptoms in patients with APS and to identify the contributing factors. METHODS: This is a prospective cohort study. Demographic, surgical, and clinical data were collected. Endoscopy was performed, and biopsies from the terminal ileum, pouch, and cuff were obtained in all patients and reviewed by a dedicated pathologist. RESULTS: Fifty-one patients with APS after IPAA were followed. Twenty patients (39.2%) had pouch-related symptoms. Single-stage IPAA had better outcomes than 2-stage IPAA: fewer daily bowel movements (42.9% vs 13.8% with ≤5 daily bowel movement, P = 0.02), more solid consistency (52.4% vs 6.9%, P < 0.001), and less abdominal pain (19% vs 48.3%, P = 0.034). Younger age at IPAA (<20) was also associated with better outcomes: fewer daily bowel movement (58.3% vs 17.9% with ≤5 daily bowel movement, P = 0.011), less watery consistency (8.3% vs 53.8%, P = 0.005), and abdominal pain (8.3% vs 43.6%, P = 0.037). Eighteen patients (35.3%) had endoscopic signs of inflammation, and 22 patients (43.1%) had histologic signs of pouchitis. However, no correlation was found between symptoms and endoscopic or histologic findings. The median pouchitis disease activity index was low (2, interquartile range 1–4) and did not correlate with clinical symptoms. DISCUSSION: Pouch-related symptoms are common in patients with APS after IPAA. One-stage IPAA and younger age at surgery are associated with better clinical outcomes. However, symptoms do not correlate well with endoscopic or histologic findings or with pouchitis disease activity index and might be attributed to a functional pouch disorder.